The Impact of Intercultural Communication on the Adaptation of Incoming Students at the Politeknik Negeri Medan - Sulaiman Ahmad; Syahrudin Marpaung; Siti Asnida Nofianna; Rehulina Bangun (International Journal of Management Research and Economics, 2024)
This research examines the influence of intercultural communication on the adaptation of new students at Politeknik Negeri Medan. As students from diverse backgrounds come together, their ability to communicate effectively across cultures becomes critical for successful adaptation. The study uses a mixed-methods approach, combining surveys and interviews, to explore the ways in which intercultural communication affects students' social and academic adaptation processes. Findings indicate that effective intercultural communication plays a significant role in promoting smoother adaptation, reducing cultural shock, and fostering inclusivity. The research contributes to understanding the role of communication skills in multicultural educational settings, providing insights for policy development to support incoming students.